Safety Profile, In Vitro Anti-Inflammatory Activity, and In Vivo Antiulcerogenic Potential of Root Barks from Annona senegalensis Pers. (Annonaceae). (6th September 2021) - Konaté, Kiessoun; Sanou, Abdoudramane; Aworet-Samseny, Raïssa R. R.; Benkhalti, Fatiha; Sytar, Oksana; Brestic, Marian; Souza, Alain; Dicko, Mamoudou Hama
Abstract : Annona senegalensis (Annonaceae) is a tropical shrub widely distributed in Burkina Faso. This plant is traditionally used as a medicine against many pathologies including typhoid fever, gastrointestinal disorders, ulcers, and inflammatory and infectious diseases. The present study was conducted to evaluate the anti-inflammatory and antiulcer properties of Annona senegalensis root bark extracts. Therefore, toxicity tests were first performed, followed by other biological tests. For this purpose, we first undertook to evaluate the toxicity tests before considering the other biological tests in a second step. The results showed that the extracted fractions had a significant effect for the different methods used (protein denaturation inhibition activity, hyaluronidase inhibition activity, and xanthine oxidase inhibition activity). However, of the extracted fractions used, the ethyl acetate fraction was the most anti-inflammatory fraction. The antiulcer activity was evaluated using the best bioactive fraction. The antiulcer effect of the ethyl acetate fraction may be due to both the reduction of gastric acid secretion and gastric cytoprotection. The results of this study also showed that the bioactive fraction reduced ethanol-induced ulceration and pyloric ligation in a dose-dependent manner, and at the highest dose (200 mg/kg), the effect was similar to that of the reference drug. In summary, the ethyl acetate fraction was found to have the best anti-inflammatory and antiulcerogenic activities. The ethyl acetate fraction at a dose of 200 mg/kg also showed a rather interesting level of cytoprotection. The anti-inflammatory and antiulcer activities could be due to the different secondary metabolites contained in the fractions extracted from Annona senegalensis, notably flavonoids, triterpenoids, steroids, saponins, and tannins. As the mechanisms of action are still little or not understood, we will consider in the future identifying the phytoconstituents and the mechanisms of action involved in the results.